An extended finite element model for modelling localised fracture of reinforced concrete beams in fire. (May 2015) - Liao, Feiyu; Huang, Zhaohui
Highlights: Develop an extended finite element model for modelling concrete beams in fire. Propose a criterion to determine the initiation of individual cracks. Consider the influence of the bond condition on the fire resistance of reinforced concrete beams. Assess the integrity of reinforced concrete beams under fire conditions. Abstract: A robust finite element procedure for modelling the localised fracture of reinforced concrete beams at elevated temperatures is developed. In this model a reinforced concrete beam is represented as an assembly of 4-node quadrilateral plain concrete, 3-node main reinforcing steel bar, and 2-node bond-link elements. The concrete element is subdivided into layers for considering the temperature distribution over the cross-section of a beam. An extended finite element method (XFEM) has been incorporated into the concrete elements in order to capture the localised cracks within the concrete. The model has been validated against previous fire test results on the concrete beams.